A tempered glass with protective function and its production process
By adding anti-heat insulation materials, modified silica, composite graphene and other materials in the production process of tempered glass, the problem of poor thermal insulation performance of existing tempered glass is solved and higher impact resistance and thermal insulation properties are achieved. , suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202311364999.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-10-20
AI Technical Summary
The existing tempered glass has poor thermal insulation performance in its application, which limits its widespread use in buildings, trains and other fields.
In the production process of tempered glass, anti-heat insulation materials are added, and modified silica and composite graphene are used in the functional layer. Through the combination of modified chitosan and graphene oxide-modified silica powder, Improve the wear resistance, impact resistance and heat insulation properties of the protective layer.
It significantly improves the impact resistance and thermal insulation performance of tempered glass, enhances the comprehensive performance of the protective layer, and is suitable for various construction and engineering applications.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tempered glass processing, and in particular to tempered glass with protective function and a production process thereof. Background Art
[0002] Glass is an amorphous inorganic non-metallic material made of quartz sand, limestone, boric acid, borax, barium carbonate, barite, feldspar, soda ash and other inorganic minerals as the main raw materials, and a small amount of auxiliary raw materials. Its main components are silicon dioxide and other oxides. Ordinary glass has low strength and will form sharp-angled fragments after breaking, posing a threat to the safety of users. In order to improve its performance, annealed glass is cut to the required size, and then treated by physical or chemical methods to obtain tempered glass with uniform compressive stress on the surface and uniform tensile stress inside. Due to the existence of internal stress, when tempered glass is subjected to load, it will first offset the surface stress, thereby improving the bearing capacity of the glass and enhancing the glass's own wind pressure resistance, cold and heat resistance, impact resistance, etc. Moreover, after being damaged by load, tempered glass will form small blunt-angled particle fragments similar to honeycombs, greatly reducing the harm to users. Therefore, tempered glass with high strength and safety is widely used in various buildings, train glass, engineering machinery, agricultural greenhouses and other fields.
[0003] Chinese invention patent (application number: 201910088048.5) discloses a high-toughness tempered glass and its preparation method, including the following raw materials by weight: 600-700 parts of quartz sand, 125-165 parts of fluorite, 90-115 parts of potassium feldspar, 75-90 parts of iron-containing composite fiber, 50-65 parts of silicon carbide fiber, 95-110 parts of aluminum oxide fiber, 35-45 parts of zinc oxide, 40-55 parts of zirconium boride, and 40-60 parts of sodium bismuth titanate. Although the invention has impact strength and bending strength, good toughness, good mechanical properties, and is not easy to damage; the surface compressive stress is large and the self-explosion rate is low, then the invention still has certain disadvantages, poor thermal insulation performance, which limits its application range.
[0004] The purpose of the present invention is to add anti-heat-insulating material to the tempered glass with good impact resistance in the prior art, so as to simultaneously improve the impact resistance and heat-insulating performance of the tempered glass. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a tempered glass with protective function and a production process thereof.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0007] A tempered glass with protective function comprises a tempered glass body and a protective layer coated on the outer layer of the tempered glass body, wherein the protective layer is solidified by a transition layer solution and a functional layer solution; the tempered glass body is composed of the following raw materials in parts by weight: 30-60 parts by weight of quartz sand, 8-20 parts by weight of feldspar, 5-15 parts by weight of soda ash, 8-20 parts by weight of limestone, 3-10 parts by weight of zinc oxide, 2-8 parts by weight of silicon carbide fiber, 0.5-2 parts by weight of titanium oxide, 1-4 parts by weight of barium carbonate, 2-5 parts by weight of borax, and 0.5-2 parts by weight of potassium metaborate.
[0008] The preparation method of the functional layer solution is as follows: 40-60 parts by weight of epoxy resin, 40-40 parts by weight of graphene or composite graphene, 0.5-1.5 parts by weight of sodium dodecyl sulfate, 0.3-1 parts by weight of sodium di(2-ethylhexyl)sulfonate succinate, 5-15 parts by weight of methacrylate, and 40-80 parts by weight of acetone are uniformly mixed, and stirred at 40-60° C. and 600-1000 rpm for 20-50 minutes to obtain the functional layer solution.
[0009] Graphene oxide is an ideal new two-dimensional material with the advantages of being non-toxic, large specific surface area, and good mechanical properties. Applying it in the functional layer can improve the wear resistance and impact resistance of the protective layer. At the same time, its good compatibility greatly improves the mixing reaction effect with other raw materials.
[0010] Silica aerogel is a three-dimensional mesh structure, loose and porous, and the conduction of heat is blocked by the gap in the hole, so that tempered glass has a good heat insulation effect; at the same time, silica can improve the wear resistance, impact resistance and the finish of the functional layer, and adding it to the material of the functional layer of tempered glass is conducive to improving the mechanical properties of the functional layer, and at the same time, nano-silicon dioxide can make the functional layer more dense and fine, and the friction coefficient becomes smaller, and the high strength of nanoparticles is added, so that the wear resistance and impact resistance of the material are greatly enhanced, and in addition, silica can also be used as a lubricant, It is an excellent flow promoter, mainly as a lubricant and a flow aid, the flatness of the protective functional layer can be further improved, but its bonding degree with graphene oxide is very low, and it is difficult to combine graphene oxide with unmodified silica sol. Therefore, the present invention modifies silica sol in the preparation process, and gives it different group energy groups on its surface, so as to be combined with the hydroxyl and carboxyl groups on the surface of graphene oxide, and improves the bonding degree between the two.
[0011] Chitosan is a natural amino polysaccharide, which is non-toxic and harmless and is widely used. It also has good film-forming and water-blocking properties. It has good film-forming properties when applied to the protective layer of tempered glass, which increases the bonding performance between the protective film and the tempered glass, thereby improving the comprehensive performance of the tempered glass.
[0012] The preparation method of the composite graphene is as follows:
[0013] S1. Dissolve graphene oxide in an ethanol aqueous solution and perform ultrasonic treatment to obtain a mixed solution a; add tetraethyl orthosilicate and perform ultrasonic treatment for 20-60 min at an ultrasonic power of 300-500 W and an ultrasonic frequency of 30-60 kHz, and then place the mixture at 30-50° C. to react for 1-3 h; then add a modifier, and then place the mixture at 50-70° C. to react for 0.5-2 h, centrifuge, wash, and dry to obtain graphene oxide-modified silicon dioxide powder;
[0014] S2, dissolving chitosan in an acetic acid aqueous solution and stirring, adding anhydrous ethanol, (RS)-3-carboxy-4-hydroxyphenylglycine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N-hydroxysuccinimide in sequence, and stirring at 30-40° C. for 16-30 hours to obtain modified chitosan;
[0015] S3, dissolving the modified chitosan in an acetic acid aqueous solution and ultrasonically treating the solution to obtain a solution b; dissolving the graphene oxide-modified silica powder in water and stirring to obtain a solution c; mixing the solution b and the solution c, stirring at 30-50° C. for 10-30 min, and obtaining a composite graphene.
[0016] Preferably, the preparation method of the composite graphene is as follows: S1, dissolving 1-4 parts by weight of graphene oxide in 80-120 parts by weight of 60-90wt% ethanol aqueous solution, ultrasonicating for 20-60min at an ultrasonic power of 300-500W and an ultrasonic frequency of 30-60kHz to obtain a mixed solution a; adjusting the pH value of the mixed solution a to 8-9 with a 0.5-2mol / L sodium hydroxide aqueous solution, adding 2-5 parts by weight of ethyl orthosilicate, ultrasonicating for 20-60min at an ultrasonic power of 300-500W and an ultrasonic frequency of 30-60kHz, and then placing at 30-50°C for reaction for 1-3h; then adding 0.3-1 parts by weight of a modifier, and then placing at 50-70°C and 200-600rpm for reaction for 0.5-2h, centrifuging, washing, and drying to obtain graphene oxide-modified silicon dioxide powder;
[0017] S2, dissolving 1-4 parts by weight of chitosan in 30-80 parts by weight of 3-10wt% acetic acid aqueous solution, ultrasonically treating for 20-60 min at an ultrasonic power of 300-500 W and an ultrasonic frequency of 30-60 kHz to obtain a solution b; dissolving 1-4 parts by weight of the above-mentioned graphene oxide-modified silica powder in 40-80 parts by weight of water, stirring at 400-800 rpm for 20-50 min to obtain a solution c; mixing solution b and solution c, stirring at 30-50° C. and 800-1200 rpm for 10-30 min, adjusting the pH to 7.5-8.5 with a 0.5-2 mol / L sodium hydroxide aqueous solution, and then ultrasonically treating for 0.5-2 h at an ultrasonic power of 300-500 W and an ultrasonic frequency of 30-60 kHz, filtering, and drying to obtain a composite graphene.
[0018] The present invention finds in the process of preparing composite graphene that the grafting rate of only chitosan and graphene oxide-modified silicon dioxide powder is not high. The possible reason is that the hydroxyl and amino groups in chitosan have high steric hindrance, which is difficult to combine with the functional group of the modifier in graphene oxide-modified silicon dioxide powder. Therefore, the inventor modifies chitosan, and uses (RS)-3-carboxyl-4-hydroxyphenylglycine containing both carboxyl and hydroxyl groups to modify chitosan. One of the carboxyl groups in (RS)-3-carboxyl-4-hydroxyphenylglycine reacts with the amino group in chitosan to obtain modified chitosan. The chitosan after modification has better active sites, which can effectively combine with the hydroxyl and carboxyl groups in graphene oxide-modified silicon dioxide powder. The prepared composite graphene not only has better film-forming performance, but also has excellent wear resistance and impact resistance, and effectively improves the comprehensive performance of the protective layer.
[0019] Specifically, S1, graphene oxide contains hydroxyl and carboxyl groups, and silica sol has a good specific surface area and adsorption performance, which can effectively adsorb graphene oxide. At the same time, the modified silica sol has hydroxyl and carboxyl groups, and can also react with part of the graphene to obtain graphene oxide-modified silica powder; S2, the amino group in chitosan can be amidated with the carboxyl group in (RS)-3-carboxyl-4-hydroxyphenylglycine to obtain modified chitosan; S3, the modified chitosan contains hydroxyl and carboxyl groups, which can effectively react and combine with the hydroxyl and carboxyl groups in the graphene-modified silica powder to finally obtain composite graphene. The composite graphene has multiple functions such as good wear resistance, impact resistance, film formation, and antibacterial, and can be effectively used in tempered glass to improve the comprehensive performance of the protective layer.
[0020] Furthermore, the preparation method of the composite graphene is as follows:
[0021] S1, dissolving 1-4 parts by weight of graphene oxide in 80-120 parts by weight of 60-90wt% ethanol aqueous solution, ultrasonicating for 20-60min at an ultrasonic power of 300-500W and an ultrasonic frequency of 30-60kHz to obtain a mixed solution a; adjusting the pH value of the mixed solution a to 8-9 with a 0.5-2mol / L sodium hydroxide aqueous solution, adding 2-5 parts by weight of ethyl orthosilicate, ultrasonicating for 20-60min at an ultrasonic power of 300-500W and an ultrasonic frequency of 30-60kHz, and then placing at 30-50°C for reaction for 1-3h; then adding 0.3-1 parts by weight of a modifier, and then placing at 50-70°C and 200-600rpm for reaction for 0.5-2h, centrifuging, washing, and drying to obtain graphene oxide-modified silicon dioxide powder;
[0022] S2, dissolving 3-8 parts by weight of chitosan in 50-120 parts by weight of 3-10wt% acetic acid aqueous solution, stirring at 400-1000rpm for 20-40min, adjusting the pH of the solution to 4.5-5.5 with 0.5-2mol / L sodium hydroxide aqueous solution, sequentially adding 30-50 parts by weight of anhydrous ethanol, 2-5 parts by weight of (RS)-3-carboxy-4-hydroxyphenylglycine, 2-5 parts by weight of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-4 parts by weight of N-hydroxysuccinimide, stirring at 30-40°C and 400-800rpm for 16-30h, dialyzing for 40-60h using a dialysis bag with a molecular weight cutoff of 6000-8000g / mol, and finally freeze-drying the dialysate to obtain modified chitosan;
[0023] S3, dissolving 1-4 parts by weight of the modified chitosan in 30-80 parts by weight of 3-10wt% acetic acid aqueous solution, ultrasonically treating for 20-60 min at an ultrasonic power of 300-500 W and an ultrasonic frequency of 30-60 kHz to obtain a solution b; dissolving 1-4 parts by weight of the graphene oxide-modified silicon dioxide powder in 40-80 parts by weight of water, stirring at 400-800 rpm for 20-50 min to obtain a solution c; mixing solution b and solution c, stirring at 30-50° C. and 800-1200 rpm for 10-30 min, adjusting the pH to 7.5-8.5 with a 0.5-2 mol / L sodium hydroxide aqueous solution, and then ultrasonically treating for 0.5-2 h at an ultrasonic power of 300-500 W and an ultrasonic frequency of 30-60 kHz, filtering, and drying to obtain a composite graphene.
[0024] The present invention adopts N-(3-triethoxysilylpropyl)-4-hydroxybutyramide containing hydroxyl group and N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane containing carboxyl group as modifiers in a certain ratio, wherein N-(3-triethoxysilylpropyl)-4-hydroxybutyramide containing hydroxyl group can react with carboxyl group in modified chitosan, and N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane containing carboxyl group can modify the performance reaction of hydroxyl group in chitosan, and the two synergize to jointly improve the comprehensive performance of the tempered glass protective layer, such as wear resistance, impact resistance, heat insulation and bonding.
[0025] The modifier is N-(3-triethoxysilylpropyl)-4-hydroxybutyramide and / or N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane; preferably, the modifier is composed of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide and N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane in a mass ratio of (2-6):(1-5); more preferably, the modifier is composed of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide and N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane in a mass ratio of 4:3;
[0026] The transition layer solution is a silica sol solution containing 10-20wt% of calcium acetate.
[0027] The production process of the tempered glass with protective function consists of the following steps:
[0028] (1) Raw material melting: Mix quartz sand, feldspar and limestone, crush them through a 200-400 mesh sieve; then mix them evenly with soda ash, zinc oxide, silicon carbide fiber, titanium oxide, barium carbonate, borax and potassium metaborate, pour them into a melting furnace for melting treatment, heat up to 1300-1500°C at 80-120°C / h, and keep them warm for 1.5-4h to obtain a molten solution;
[0029] (2) Processing and molding: The molten solution is rolled into a flat glass with a thickness of 3-12 mm, and then cooled and molded at room temperature to obtain molded glass;
[0030] (3) Tempering treatment: a 5-15 μm transition layer solution is uniformly coated on the surface of the above-mentioned molded glass to form a transition layer, and the layer is cured at 130-160°C for 10-40 min, and then kept in an argon atmosphere at 700-800°C for 5-15 min, and naturally cooled to room temperature to obtain porous tempered glass;
[0031] (4) Functionalization treatment: A layer of functional layer solution with a thickness of 40-100 μm is coated on the surface of the porous tempered glass to form a functional layer, which is then cured at 130-150° C. for 30-60 min to obtain a tempered glass with protective function.
[0032] Beneficial effects of the invention:
[0033] 1. The present invention coats a layer of silica gel porous insulation layer before coating the functional layer, which not only improves the bonding strength between the functional coating and the tempered glass, significantly enhances the scratch resistance and impact resistance of the functional coating, but also has the barrier function of the closed insulation pores to heat transfer, thereby improving the insulation effect of the tempered glass.
[0034] 2. The present invention adds composite graphene to the functional layer, and coating it on the tempered glass not only has good film-forming properties, but also has excellent wear resistance and impact resistance. The coating structure will not be destroyed, and the comprehensive performance of the protective layer is effectively improved. DETAILED DESCRIPTION
[0035] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0036] Introduction of some raw materials in this application:
[0037] Graphene oxide was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S28018.
[0038] Chitosan was purchased from Baoji Fangsheng Biological Development Co., Ltd., with a deacetylation degree ≥ 85%, item number: FS-KJT.
[0039] Quartz sand was purchased from Shenzhen Zhenchun Environmental Protection Technology Co., Ltd., model: ZCL-S.
[0040] Feldspar was purchased from Hebei Hengguang Mineral Products Co., Ltd., mesh number: 100 mesh.
[0041] Limestone was purchased from Hefei Jiankun Chemical Co., Ltd., item number: 10005760.
[0042] Silicon carbide fiber was purchased from Qinghe County Andy Metal Materials Co., Ltd., with a particle size of 150-3000.
[0043] Silica sol was purchased from Dongguan Huihe Yongsheng Nanotechnology Co., Ltd., specification: SDW-3030.
[0044] Epoxy resin was purchased from Langfang Tuxin Anticorrosion Materials Co., Ltd., item number: HHTX-2022030306. Example
[0045] A tempered glass with protective function, comprising a tempered glass body and a protective layer coated on the outer layer of the tempered glass body, wherein the tempered glass body is composed of the following raw materials in parts by weight: 45 parts by weight of quartz sand, 12 parts by weight of feldspar, 10 parts by weight of soda ash, 12 parts by weight of limestone, 5 parts by weight of zinc oxide, 4 parts by weight of silicon carbide fiber, 1 part by weight of titanium oxide, 2 parts by weight of barium carbonate, 3 parts by weight of borax, and 1 part by weight of potassium metaborate; the protective layer is solidified by a transition layer solution and a functional layer solution;
[0046] The transition layer solution is a silica sol solution containing 15wt% calcium acetate;
[0047] The functional layer solution is prepared as follows: 50 parts by weight of epoxy resin, 30 parts by weight of graphene oxide, 0.8 parts by weight of sodium dodecyl sulfate, 0.6 parts by weight of sodium di(2-ethylhexyl)sulfosuccinate, 10 parts by weight of methacrylate, and 60 parts by weight of acetone are uniformly mixed, and stirred at 50° C. and 800 rpm for 30 minutes to obtain the functional layer solution.
[0048] The production process of the tempered glass with protective function consists of the following steps:
[0049] (1) Raw material melting: Mix quartz sand, feldspar and limestone, crush them and pass through a 300-mesh sieve; then mix them evenly with soda ash, zinc oxide, silicon carbide fiber, titanium oxide, barium carbonate, borax and potassium metaborate, pour them into a furnace for melting treatment, heat them at 100°C / h to 1400°C, keep them warm for 2h, and obtain a molten solution;
[0050] (2) Processing and molding: The molten solution is rolled into a flat glass with a thickness of 5 mm, and then cooled and molded at room temperature to obtain molded glass;
[0051] (3) Tempering treatment: a 10 μm transition layer solution is uniformly coated on the surface of the molded glass to form a transition layer, which is cured at 150°C for 20 min, then kept in an argon atmosphere at 750°C for 10 min, and naturally cooled to room temperature to obtain a porous tempered glass;
[0052] (4) Functionalization treatment: A layer of 80 μm functional layer solution is coated on the surface of the porous tempered glass to form a functional layer, which is then cured at 140° C. for 40 min to obtain a tempered glass with protective function. Example
[0053] A tempered glass with protective function, comprising a tempered glass body and a protective layer coated on the outer layer of the tempered glass body, wherein the tempered glass body is composed of the following raw materials in parts by weight: 45 parts by weight of quartz sand, 12 parts by weight of feldspar, 10 parts by weight of soda ash, 12 parts by weight of limestone, 5 parts by weight of zinc oxide, 4 parts by weight of silicon carbide fiber, 1 part by weight of titanium oxide, 2 parts by weight of barium carbonate, 3 parts by weight of borax, and 1 part by weight of potassium metaborate; the protective layer is solidified by a transition layer solution and a functional layer solution;
[0054] The transition layer solution is a silica sol solution containing 15wt% calcium acetate;
[0055] The functional layer solution is prepared as follows: 50 parts by weight of epoxy resin, 30 parts by weight of composite graphene, 0.8 parts by weight of sodium dodecyl sulfate, 0.6 parts by weight of sodium di(2-ethylhexyl)sulfosuccinate, 10 parts by weight of methyl methacrylate, and 60 parts by weight of acetone are uniformly mixed, and stirred at 50° C. and 800 rpm for 30 minutes to obtain the functional layer solution.
[0056] The preparation method of the composite graphene is as follows: 2 parts by weight of graphene oxide is dissolved in 100 parts by weight of 80wt% ethanol aqueous solution, and ultrasonically treated for 40 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz to obtain a mixed solution a; the pH value of the mixed solution a is adjusted to 8.5 with a 1mol / L sodium hydroxide aqueous solution, 3 parts by weight of ethyl orthosilicate is added, and ultrasonically treated for 30 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz, and then placed at 40°C for reaction for 2 hours, centrifuged, washed, and dried to obtain the composite graphene.
[0057] The production process of the tempered glass with protective function consists of the following steps:
[0058] (1) Raw material melting: Mix quartz sand, feldspar and limestone, crush them and pass through a 300-mesh sieve; then mix them evenly with soda ash, zinc oxide, silicon carbide fiber, titanium oxide, barium carbonate, borax and potassium metaborate, pour them into a furnace for melting treatment, heat them at 100°C / h to 1400°C, keep them warm for 2h, and obtain a molten solution;
[0059] (2) Processing and molding: The molten solution is rolled into a flat glass with a thickness of 5 mm, and then cooled and molded at room temperature to obtain molded glass;
[0060] (3) Tempering treatment: a 10 μm transition layer solution is uniformly coated on the surface of the molded glass to form a transition layer, which is cured at 150°C for 20 min, then kept in an argon atmosphere at 750°C for 10 min, and naturally cooled to room temperature to obtain a porous tempered glass;
[0061] (4) Functionalization treatment: A layer of 80 μm functional layer solution is coated on the surface of the porous tempered glass to form a functional layer, which is then cured at 140° C. for 40 min to obtain a tempered glass with protective function. Example
[0062] A tempered glass with protective function, comprising a tempered glass body and a protective layer coated on the outer layer of the tempered glass body, wherein the tempered glass body is composed of the following raw materials in parts by weight: 45 parts by weight of quartz sand, 12 parts by weight of feldspar, 10 parts by weight of soda ash, 12 parts by weight of limestone, 5 parts by weight of zinc oxide, 4 parts by weight of silicon carbide fiber, 1 part by weight of titanium oxide, 2 parts by weight of barium carbonate, 3 parts by weight of borax, and 1 part by weight of potassium metaborate; the protective layer is solidified by a transition layer solution and a functional layer solution;
[0063] The transition layer solution is a silica sol solution containing 15wt% calcium acetate;
[0064] The functional layer solution is prepared as follows: 50 parts by weight of epoxy resin, 30 parts by weight of composite graphene, 0.8 parts by weight of sodium dodecyl sulfate, 0.6 parts by weight of sodium di(2-ethylhexyl)sulfosuccinate, 10 parts by weight of methyl methacrylate, and 60 parts by weight of acetone are uniformly mixed, and stirred at 50° C. and 800 rpm for 30 minutes to obtain the functional layer solution.
[0065] The preparation method of the composite graphene is as follows: 2 parts by weight of graphene oxide is dissolved in 100 parts by weight of 80wt% ethanol aqueous solution, and ultrasonically treated for 40 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz to obtain a mixed solution a; the pH value of the mixed solution a is adjusted to 8.5 with a 1mol / L sodium hydroxide aqueous solution, 3 parts by weight of ethyl orthosilicate is added, and ultrasonically treated for 30 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz, and then placed at 40°C for reaction for 2 hours; then 0.5 parts by weight of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide is added, and then placed at 60°C and 400rpm for reaction for 1 hour, centrifuged, washed, and dried to obtain the composite graphene.
[0066] The production process of the tempered glass with protective function consists of the following steps:
[0067] (1) Raw material melting: Mix quartz sand, feldspar and limestone, crush them and pass through a 300-mesh sieve; then mix them evenly with soda ash, zinc oxide, silicon carbide fiber, titanium oxide, barium carbonate, borax and potassium metaborate, pour them into a furnace for melting treatment, heat them at 100°C / h to 1400°C, keep them warm for 2h, and obtain a molten solution;
[0068] (2) Processing and molding: The molten solution is rolled into a flat glass with a thickness of 5 mm, and then cooled and molded at room temperature to obtain molded glass;
[0069] (3) Tempering treatment: a 10 μm transition layer solution is uniformly coated on the surface of the molded glass to form a transition layer, which is cured at 150°C for 20 min, then kept in an argon atmosphere at 750°C for 10 min, and naturally cooled to room temperature to obtain a porous tempered glass;
[0070] (4) Functionalization treatment: A layer of 80 μm functional layer solution is coated on the surface of the porous tempered glass to form a functional layer, which is then cured at 140° C. for 40 min to obtain a tempered glass with protective function. Example
[0071] A tempered glass with protective function, comprising a tempered glass body and a protective layer coated on the outer layer of the tempered glass body, wherein the tempered glass body is composed of the following raw materials in parts by weight: 45 parts by weight of quartz sand, 12 parts by weight of feldspar, 10 parts by weight of soda ash, 12 parts by weight of limestone, 5 parts by weight of zinc oxide, 4 parts by weight of silicon carbide fiber, 1 part by weight of titanium oxide, 2 parts by weight of barium carbonate, 3 parts by weight of borax, and 1 part by weight of potassium metaborate; the protective layer is solidified by a transition layer solution and a functional layer solution;
[0072] The transition layer solution is a silica sol solution containing 15wt% calcium acetate;
[0073] The functional layer solution is prepared as follows: 50 parts by weight of epoxy resin, 30 parts by weight of composite graphene, 0.8 parts by weight of sodium dodecyl sulfate, 0.6 parts by weight of sodium di(2-ethylhexyl)sulfosuccinate, 10 parts by weight of methyl methacrylate, and 60 parts by weight of acetone are uniformly mixed, and stirred at 50° C. and 800 rpm for 30 minutes to obtain the functional layer solution.
[0074] The preparation method of the composite graphene is as follows:
[0075] S1: 2 parts by weight of graphene oxide are dissolved in 100 parts by weight of 80wt% ethanol aqueous solution, and ultrasonically treated for 40 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz to obtain a mixed solution a; the pH value of the mixed solution a is adjusted to 8.5 with a 1 mol / L sodium hydroxide aqueous solution, 3 parts by weight of ethyl orthosilicate are added, and ultrasonically treated for 30 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz, and then reacted at 40°C for 2 hours; then 0.5 parts by weight of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide are added, and then reacted at 60°C and 400rpm for 1 hour, centrifuged, washed, and dried to obtain graphene oxide-modified silica powder;
[0076] S2, 2 parts by weight of chitosan were dissolved in 50 parts by weight of 5wt% acetic acid aqueous solution, and ultrasonicated for 30 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz to obtain a solution b; 2 parts by weight of the above-mentioned graphene oxide-modified silica powder were dissolved in 60 parts by weight of water, and stirred at 600rpm for 30min to obtain a solution c; solution b and solution c were mixed, stirred at 40°C and 1000rpm for 20min, the pH was adjusted to 8 with a 1mol / L sodium hydroxide aqueous solution, and then ultrasonicated for 1h at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz, filtered and dried to obtain a composite graphene.
[0077] The production process of the tempered glass with protective function consists of the following steps:
[0078] (1) Raw material melting: Mix quartz sand, feldspar and limestone, crush them and pass through a 300-mesh sieve; then mix them evenly with soda ash, zinc oxide, silicon carbide fiber, titanium oxide, barium carbonate, borax and potassium metaborate, pour them into a furnace for melting treatment, heat them at 100°C / h to 1400°C, keep them warm for 2h, and obtain a molten solution;
[0079] (2) Processing and molding: The molten solution is rolled into a flat glass with a thickness of 5 mm, and then cooled and molded at room temperature to obtain molded glass;
[0080] (3) Tempering treatment: a 10 μm transition layer solution is uniformly coated on the surface of the molded glass to form a transition layer, which is cured at 150°C for 20 min, then kept in an argon atmosphere at 750°C for 10 min, and naturally cooled to room temperature to obtain a porous tempered glass;
[0081] (4) Functionalization treatment: A layer of 80 μm functional layer solution is coated on the surface of the porous tempered glass to form a functional layer, which is then cured at 140° C. for 40 min to obtain a tempered glass with protective function. Example
[0082] A tempered glass with protective function, comprising a tempered glass body and a protective layer coated on the outer layer of the tempered glass body, wherein the tempered glass body is composed of the following raw materials in parts by weight: 45 parts by weight of quartz sand, 12 parts by weight of feldspar, 10 parts by weight of soda ash, 12 parts by weight of limestone, 5 parts by weight of zinc oxide, 4 parts by weight of silicon carbide fiber, 1 part by weight of titanium oxide, 2 parts by weight of barium carbonate, 3 parts by weight of borax, and 1 part by weight of potassium metaborate; the protective layer is solidified by a transition layer solution and a functional layer solution;
[0083] The transition layer solution is a silica sol solution containing 15wt% calcium acetate;
[0084] The functional layer solution is prepared as follows: 50 parts by weight of epoxy resin, 30 parts by weight of composite graphene, 0.8 parts by weight of sodium dodecyl sulfate, 0.6 parts by weight of sodium di(2-ethylhexyl)sulfosuccinate, 10 parts by weight of methyl methacrylate, and 60 parts by weight of acetone are uniformly mixed, and stirred at 50° C. and 800 rpm for 30 minutes to obtain the functional layer solution.
[0085] The preparation method of the composite graphene is as follows:
[0086] S1. Dissolve 2 parts by weight of graphene oxide in 100 parts by weight of 80wt% ethanol aqueous solution, and ultrasonicate for 40 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz to obtain a mixed solution a; adjust the pH value of the mixed solution a to 8.5 with a 1 mol / L sodium hydroxide aqueous solution, add 3 parts by weight of ethyl orthosilicate, and ultrasonicate for 30 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz, and then place it at 40°C for reaction for 2 hours; then add 0.5 parts by weight of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide, and then place it at 60°C and 400rpm for reaction for 1 hour, centrifuge, wash, and dry to obtain graphene oxide-modified silicon dioxide powder;
[0087] S2, 5 parts by weight of chitosan were dissolved in 80 parts by weight of 5wt% acetic acid aqueous solution, stirred at 600rpm for 30min, the pH of the solution was adjusted to 5 with 1mol / L sodium hydroxide aqueous solution, 40 parts by weight of anhydrous ethanol, 2.8 parts by weight of (RS)-3-carboxy-4-hydroxyphenylglycine, 3 parts by weight of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 2 parts by weight of N-hydroxysuccinimide were added in sequence, stirred at 35°C and 600rpm for 20h, dialyzed for 48h using a dialysis bag with a molecular weight cutoff of 7000g / mol, and finally the dialyzate was freeze-dried to obtain modified chitosan;
[0088] S3, dissolving 2 parts by weight of the modified chitosan in 50 parts by weight of 5wt% acetic acid aqueous solution, ultrasonically treating for 30 min at an ultrasonic power of 400 W and an ultrasonic frequency of 45 kHz to obtain a solution b; dissolving 2 parts by weight of the graphene oxide-modified silica powder in 60 parts by weight of water, stirring at 600 rpm for 30 min to obtain a solution c; mixing solution b and solution c, stirring at 40°C and 1000 rpm for 20 min, adjusting the pH to 8 with a 1 mol / L sodium hydroxide aqueous solution, and then ultrasonically treating for 1 h at an ultrasonic power of 400 W and an ultrasonic frequency of 45 kHz, filtering, and drying to obtain a composite graphene.
[0089] The production process of the tempered glass with protective function consists of the following steps:
[0090] (1) Raw material melting: Mix quartz sand, feldspar and limestone, crush them and pass through a 300-mesh sieve; then mix them evenly with soda ash, zinc oxide, silicon carbide fiber, titanium oxide, barium carbonate, borax and potassium metaborate, pour them into a furnace for melting treatment, heat them at 100°C / h to 1400°C, keep them warm for 2h, and obtain a molten solution;
[0091] (2) Processing and molding: The molten solution is rolled into a flat glass with a thickness of 5 mm, and then cooled and molded at room temperature to obtain molded glass;
[0092] (3) Tempering treatment: a 10 μm transition layer solution is uniformly coated on the surface of the molded glass to form a transition layer, which is cured at 150°C for 20 min, then kept in an argon atmosphere at 750°C for 10 min, and naturally cooled to room temperature to obtain a porous tempered glass;
[0093] (4) Functionalization treatment: A layer of 80 μm functional layer solution is coated on the surface of the porous tempered glass to form a functional layer, which is then cured at 140° C. for 40 min to obtain a tempered glass with protective function. Example
[0094] The method is basically the same as Example 5, except that the preparation method of the composite graphene is as follows:
[0095] S1. Dissolve 2 parts by weight of graphene oxide in 100 parts by weight of 80wt% ethanol aqueous solution, and ultrasonicate for 40 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz to obtain a mixed solution a; adjust the pH value of the mixed solution a to 8.5 with a 1 mol / L sodium hydroxide aqueous solution, add 3 parts by weight of ethyl orthosilicate, and ultrasonicate for 30 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz, and then place it at 40°C for reaction for 2 hours; then add 0.5 parts by weight of N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane, and then place it at 60°C and 400rpm for reaction for 1 hour, centrifuge, wash, and dry to obtain graphene oxide-modified silicon dioxide powder;
[0096] S2, 5 parts by weight of chitosan were dissolved in 80 parts by weight of 5wt% acetic acid aqueous solution, stirred at 600rpm for 30min, the pH of the solution was adjusted to 5 with 1mol / L sodium hydroxide aqueous solution, 40 parts by weight of anhydrous ethanol, 2.8 parts by weight of (RS)-3-carboxy-4-hydroxyphenylglycine, 3 parts by weight of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 2 parts by weight of N-hydroxysuccinimide were added in sequence, stirred at 35°C and 600rpm for 20h, dialyzed for 48h using a dialysis bag with a molecular weight cutoff of 7000g / mol, and finally the dialyzate was freeze-dried to obtain modified chitosan;
[0097] S3, dissolving 2 parts by weight of the modified chitosan in 50 parts by weight of 5wt% acetic acid aqueous solution, ultrasonically treating for 30 min at an ultrasonic power of 400 W and an ultrasonic frequency of 45 kHz to obtain a solution b; dissolving 2 parts by weight of the graphene oxide-modified silica powder in 60 parts by weight of water, stirring at 600 rpm for 30 min to obtain a solution c; mixing solution b and solution c, stirring at 40°C and 1000 rpm for 20 min, adjusting the pH to 8 with a 1 mol / L sodium hydroxide aqueous solution, and then ultrasonically treating for 1 h at an ultrasonic power of 400 W and an ultrasonic frequency of 45 kHz, filtering, and drying to obtain a composite graphene. Example
[0098] The method is basically the same as Example 5, except that the preparation method of the composite graphene is as follows:
[0099] S1, 2 parts by weight of graphene oxide are dissolved in 100 parts by weight of 80wt% ethanol aqueous solution, and ultrasonicated for 40 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz to obtain a mixed solution a; the pH value of the mixed solution a is adjusted to 8.5 with a 1 mol / L sodium hydroxide aqueous solution, 3 parts by weight of ethyl orthosilicate are added, and ultrasonicated for 30 minutes at an ultrasonic power of 400W and an ultrasonic frequency of 45kHz, and then placed at 40°C for reaction for 2 hours; then 0.5 parts by weight of a modifier is added, and then placed at 60°C and 400rpm for reaction for 1 hour, centrifuged, washed, and dried to obtain graphene oxide-modified silicon dioxide powder; the modifier is composed of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide and N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane in a mass ratio of 4:3;
[0100] S2, 5 parts by weight of chitosan were dissolved in 80 parts by weight of 5wt% acetic acid aqueous solution, stirred at 600rpm for 30min, the pH of the solution was adjusted to 5 with 1mol / L sodium hydroxide aqueous solution, 40 parts by weight of anhydrous ethanol, 2.8 parts by weight of (RS)-3-carboxy-4-hydroxyphenylglycine, 3 parts by weight of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 2 parts by weight of N-hydroxysuccinimide were added in sequence, stirred at 35°C and 600rpm for 20h, dialyzed for 48h using a dialysis bag with a molecular weight cutoff of 7000g / mol, and finally the dialyzate was freeze-dried to obtain modified chitosan;
[0101] S3, dissolving 2 parts by weight of the modified chitosan in 50 parts by weight of 5wt% acetic acid aqueous solution, ultrasonically treating for 30 min at an ultrasonic power of 400 W and an ultrasonic frequency of 45 kHz to obtain a solution b; dissolving 2 parts by weight of the graphene oxide-modified silica powder in 60 parts by weight of water, stirring at 600 rpm for 30 min to obtain a solution c; mixing solution b and solution c, stirring at 40°C and 1000 rpm for 20 min, adjusting the pH to 8 with a 1 mol / L sodium hydroxide aqueous solution, and then ultrasonically treating for 1 h at an ultrasonic power of 400 W and an ultrasonic frequency of 45 kHz, filtering, and drying to obtain a composite graphene.
[0102] Impact resistance test: The impact resistance test in accordance with the national standard GB5137.1-2020 "Test methods for automotive safety glass - Part 1: Mechanical properties test" was used for the test. Test conditions: temperature: 20°C, relative humidity: 50%, impact height: 2000mm, steel ball mass: 226g. The test was conducted 5 times in parallel and the average value was taken. The test results are shown in Table 1.
[0103] As can be seen from the results of the above embodiments, silicon dioxide can improve the wear resistance, impact resistance and smoothness of the functional layer. Adding it to the material of the functional layer of tempered glass is conducive to improving the mechanical properties of the functional layer. At the same time, nano silicon dioxide can make the functional layer more dense and fine, and the friction coefficient becomes smaller. In addition, the high strength of nanoparticles greatly enhances the wear resistance and impact resistance of the material. In addition, silicon dioxide can also be used as a lubricant to further improve the flatness of the protective functional layer, but its bonding degree with graphene oxide is very low, and it is difficult to combine graphene oxide with unmodified silicon dioxide sol. Therefore, the present invention modifies the silicon dioxide sol in the preparation process, and gives it different energy groups on the surface, so as to facilitate the combination with the hydroxyl and carboxyl groups on the surface of graphene oxide, improve the bonding degree between the two, and improve the impact resistance of tempered glass.
[0104] In Example 4, the grafting rate of chitosan and graphene oxide-modified silica powder is not high. The possible reason is that the hydroxyl and amino groups in chitosan have high steric hindrance, which is difficult to combine with the functional groups of the modifier in the graphene oxide-modified silica powder. In Example 5, modified chitosan is used for modification. (RS)-3-carboxyl-4-hydroxyphenylglycine containing both carboxyl and hydroxyl groups is used to modify chitosan. One of the carboxyl groups in (RS)-3-carboxyl-4-hydroxyphenylglycine reacts with the amino group in chitosan to obtain modified chitosan. The modified chitosan has better active sites and can effectively combine with the hydroxyl and carboxyl groups in the graphene oxide-modified silica powder. The prepared composite graphene not only has better film-forming properties, but also has excellent wear resistance and impact resistance.
[0105] In Example 6, N-(3-triethoxysilylpropyl)-4-hydroxybutyramide containing a hydroxyl group and N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane containing a carboxyl group are used as modifiers in a certain ratio. The hydroxyl-containing N-(3-triethoxysilylpropyl)-4-hydroxybutyramide can react with the carboxyl group in the modified chitosan, while the carboxyl N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane can modify the hydroxyl performance reaction in the chitosan. The two synergize to jointly improve the comprehensive performance of the tempered glass protective layer, such as impact resistance and bonding.
[0106] Thermal insulation performance test: refer to Appendix A thermal insulation temperature difference test method in T / CADBM 9-2019 "Quality Assessment Standard for Glass Insulation Coatings" for testing, and carry out thermal insulation temperature difference test on each embodiment of the present application. The tempered glass plate without functional layer coated on the surface is used as the standard plate in the thermal insulation temperature difference test method. Embodiments 1-7 are test pieces. The test sample size is 314mm×314mm×5mm. The test environment is 23°C and the relative humidity is 50%. Each group of samples is tested in parallel 3 times and the average value is taken. The test results are shown in Table 2 below.
[0107] From the above results, it can be seen that the tempered glass prepared by the present invention has a very good thermal insulation temperature difference. Starting from Example 4, the thermal insulation temperature difference can reach 50 ≥ 9.0, because the silica aerogel has a three-dimensional network structure, which is loose and porous, and the conduction of heat is blocked by the gaps in the pores, so that the tempered glass has a good thermal insulation effect.
Claims
1. A tempered glass with protective function, comprising a tempered glass body and a protective layer coated on the outer layer of the tempered glass body, characterized in that: The protective layer is formed by curing the transition layer solution and the functional layer solution; the preparation method of the functional layer solution is as follows: epoxy resin, composite graphene, sodium dodecyl sulfate, sodium di(2-ethylhexyl)sulfosuccinate, methacrylate, and acetone are uniformly mixed and stirred to obtain the functional layer solution; The preparation method of the composite graphene is as follows: S1. Dissolve graphene oxide in ethanol aqueous solution and perform ultrasonic treatment to obtain a mixed solution a; add tetraethyl orthosilicate and perform ultrasonic treatment at an ultrasonic power of 300-500 W and an ultrasonic frequency of 30-60 kHz for 20-60 min, and then place the mixture at 30-50° C. to react for 1-3 h; then add a modifier, and place the mixture at 50-70° C. to react for 0.5-2 h, centrifuge, wash, and dry to obtain graphene oxide-modified silicon dioxide powder; the modifier is composed of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide and N-[β-(N,N-diacetoxy)aminoethyl]-γ-(N-acetoxy)aminopropyltrimethoxysilane in a mass ratio of (2-6):(1-5); S2, dissolving chitosan in an acetic acid aqueous solution and stirring, adding anhydrous ethanol, (RS)-3-carboxy-4-hydroxyphenylglycine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N-hydroxysuccinimide in sequence, and stirring at 30-40° C. for 16-30 hours to obtain modified chitosan; S3, dissolving the modified chitosan in an acetic acid aqueous solution and ultrasonically obtaining a solution b; dissolving the graphene oxide-modified silica powder in water and stirring to obtain a solution c; mixing the solution b and the solution c, stirring at 30-50° C. for 10-30 min, to obtain a composite graphene; The transition layer solution is a silica sol solution containing calcium acetate.
2. The tempered glass with protective function as claimed in claim 1, characterized in that: The tempered glass body is composed of the following raw materials in parts by weight: 30-60 parts by weight of quartz sand, 8-20 parts by weight of feldspar, 5-15 parts by weight of soda ash, 8-20 parts by weight of limestone, 3-10 parts by weight of zinc oxide, 2-8 parts by weight of silicon carbide fiber, 0.5-2 parts by weight of titanium oxide, 1-4 parts by weight of barium carbonate, 2-5 parts by weight of borax, and 0.5-2 parts by weight of potassium metaborate.
3. The production process of tempered glass with protective function as claimed in claim 1 or 2, characterized in that: It consists of the following steps: (1) Raw material melting: quartz sand, feldspar and limestone are mixed, crushed and sieved; then mixed evenly with soda ash, zinc oxide, silicon carbide fiber, titanium oxide, barium carbonate, borax and potassium metaborate, poured into a melting furnace for melting treatment to obtain a molten solution; (2) Processing and molding: The molten solution is rolled into flat glass, which is then cooled and molded at room temperature to obtain molded glass; (3) Tempering treatment: uniformly coating a transition layer solution on the surface of the molded glass to form a transition layer, performing a curing treatment, and naturally cooling to room temperature to obtain a porous tempered glass; (4) Functionalization treatment: a functional layer solution is coated on the surface of the porous tempered glass to form a functional layer, and then cured to obtain a tempered glass with protective function.
Citation Information
Patent Citations
A high-toughness tempered glass and its preparation method
CN109574499B
Preparation method for graphene-silicon dioxide aerogel
CN107235744A
High-toughness tempered glass and preparation method thereof
CN109574499A
Toughened glass thermal insulation coating and preparation method thereof
CN112408763A